Ask Prices, Offers, and Time to Sale in an Online Exchange. - Farmer, Amy; Stango, Victor (Economic Inquiry, 2004)
By examining an online computer exchange, we find that sellers who place higher nonbinding ask prices have higher outstanding offers and remain on the exchange longer, suggesting a willingness to hold out for higher offers. Additionally, higher ask prices deter buyers from making offers. The results are stronger in thinner market segments, suggesting that gains from waiting for a high price are greater when buyers' tastes are idiosyncratic. These relationships are consistent with models in which buyers engage in costly search and suggest that online exchanges may not eliminate the frictions related to bilateral transactions. Reprinted by permission of the publisher.